Migration and Jobs : Issues for the 21st Century - Christiaensen, Luc (World Bank, Washington, DC, 2019)
With an estimated 724 million extreme poor people living in developing countries, and the world's demographics bifurcating into an older North and a younger South, there are substantial economic incentives and benefits for people to migrate. There are also important market and regulatory failures that constrain mobility and reduce the net benefits of migration. This paper reviews the recent literature and proposes a conceptual framework for better integration and coordination of policies that can address the different market and regulatory failures. The paper advances five types of interventions in need of particular attention in design, implementation, and evaluation; namely, (1) active labor market programs that serve local, regional, and foreign markets; (2) remittances and investment subsidies to promote job creation and labor productivity growth; (3) social insurance programs that cover all jobs and facilitate labor mobility; (4) labor taxes to internalize the social costs of migration in receiving regions; and (5) more flexible private sector driven schemes to regulate the flow of migrants and minimize irregular migration.